Strategi Digitalisasi PSDM Pada Baitul Maal Muamalat Untuk Mendukung Pemberdayaan Masyarakat - Prayoga, Achmad Rian Agung; Aini, Saqofa Nabilah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2025)
This study aims to analyze the digitalization strategy of human resource development (HRD) implemented by Baitulmaal Muamalat (BMM) in supporting the effectiveness of community empowerment programs. Digital transformation in HR management is a strategic aspect to improve the internal capabilities of Islamic philanthropic institutions in responding to the challenges of the Industrial Revolution 4.0 and the Society 5.0 era. This study uses a qualitative descriptive method with data collection through in-depth interviews, direct observation, and internal documentation of the institution. The results of the study indicate that the HRD digitalization strategy at BMM is carried out through technology-based training, strengthening the role of the young generation of digital natives in program management, and utilizing internal applications (SiBam) for performance evaluation and control. The findings also show that the implementation of this digital strategy has an impact on increasing work efficiency, program target accuracy, and expanding the reach of beneficiaries. Based on these results, it can be concluded that HR digitalization not only increases the operational effectiveness of the institution but also strengthens the leverage of sustainable economic empowerment programs. This study is expected to be a reference for Islamic social and financial institutions in designing digital strategies that are adaptive and have a broad impact on society.